Subsarcomeric regulation of thin and thick filaments in skeletal muscle myofibrils - Kristina Sliogeryte; Luca Fusi (Proceedings of the National Academy of Sciences, 2026)
Muscle contraction relies on the coordinated activation of myosin motors from a folded-OFF state on the thick filament surface and their actin tracks on the thin filaments in response to calcium. Thick filaments contain distinct regulatory zones defined by the presence of myosin-binding protein C (MyBP-C) and titin super-repeats, but the control of myosin OFF/ON states within these zones has not been directly resolved. Here, we do so by fluorescence polarization microscopy (FPM) in myofibrils isolated from rabbit fast skeletal muscle. Using orientation-specific probes on myosin we show that folded-OFF motors are enriched in the MyBP-C–containing C zone in relaxed myofibrils, indicating that MyBP-C stabilizes the myosin OFF state in this filament domain. Under titin-based passive tension or partial calcium activation, active motors are enriched in the D zone at the filament tips, which lacks MyBP-C, suggesting that D-zone motors are activated at lower filament stress. Troponin probes further reveal that myosin enhances thin-filament activation in the region of filament overlap and drives the stress-dependent activation of the thin filament into adjacent nonoverlap regions. These findings uncover zone-specific control of myofilament activation within the sarcomere and establish FPM as a powerful tool for investigating disease-linked myofilament protein variants and therapeutic modulation.